Juvenile Idiopathic Arthritis-associated Uveitis at an Italian Tertiary Referral Center: Clinical Features and Complications. (February 2015) - Paroli, Maria Pia; Abbouda, Alessandro; Restivo, Lucia; Sapia, Alfredo; Abicca, Irene; Pivetti Pezzi, Paola
Abstract Purpose: To describe the frequencies and risk factors of ocular complications and poor visual outcomes in children with juvenile idiopathic arthritis (JIA). Methods: Retrospective cohort study, including 69 consecutive children (116 eyes) affected by JIA-associated uveitis managed at a tertiary uveitis clinic. Results: The incidence of visual loss to the 20/50 or worse threshold was 0.04/eye-year (EY) and to the 20/200 or worse threshold was 0.02/EY. The most common complications at baseline were posterior synechiae (52%), band keratopathy (38%), and cataract (12%). Risk factor for a visual acuity threshold of 20/50 or worse included hypotony (p = 0.01; hazard ratio [HR] 3.7; 95% CI 1.3–10.4); anterior chamber flare >1 (p = 0.04; HR 1.3; 95% CI 0.5–3.4); a positive antinuclear antibody (ANA) (p = 0.02; HR1.4; 95% CI 0.8–2.4). Hypotony and positive ANA are also associated to the 20/200 or worse threshold (p = 0.03; HR 5.1; 95% CI 1.1–23.9 and p = 0.04; HR 1.0; 95% CI 0.4–2.3; respectively). Use of immunosuppressive drugs was associated with a reduced risk of visual loss of 20/200 or worse (odds ratio 0.14, 95% CI, 0.02–1.29; p = 0.04). Conclusions: Loss of vision and ocular complications still occur among children with JIA-related uveitis. Prompt diagnosis and a strict follow up associated to immunosuppressive therapy may decrease the poor visual outcome.